(untitled) (Theatrum historiae, 2020)
The presented study deals with the matter of the material provision of the first and second generation of Protestant preachers following the issue of the Patent of Toleration. The first generation of preachers was, exclusively, of Hungarian origin, while the second one was represented by preachers coming from the domestic, Czech background. Solely the faithful were responsible for the livelihood of Protestant preachers. On the basis of comparison of both generations’ lists of contributions, assessment of the country’s economic situation and the strength of the then currency, we are able to find out what their financial state was. The first-generation preachers are traditionally viewed as poor pastors who, because of poverty, often changed church communities or abandoned the Czech provinces. The situation of the second-generation preachers is not known so well, however, usually a stable and secure position is attributed to them. Looking closer at both the generations, it is evident that in neither of them the financial state of preachers was definite and their material provision did not depend so much on the amount of service but on the broader economic and social aspects.